Organic Amino Acids Chelates; Preparation, Spectroscopic Characterization and Applications as Foliar Fertilizers (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Cu(II) complexes of amino acid hydrolyzate soya protein isolate have been prepared. In order to study the mode of coordination in the above chelates and their effect as foliar fertilizer, Mn(II), Co(II), Nil(II), Cu(II), Zn(II) and Cd(II) complexes of Â L-mino acids have been prepared and characterized by elemental and spectral analyses,( IR, UV-VIS, mass spectra and ESR), electrical conductance, magnetic moments and thermal analyses (DTA and TGA). ESR spectra of copper (II) complexes show isotropic and anisotropic types d(x2-y2) with covalent bond character. The amino acids chelates were evaluated as foliar fertilizer by treating plants with micronutrient, amino acid solutions and varying concentrations of micronutrient amino acids chelats. It was found that spraying plant with 2.5% micronutrient amino acids chelats gives the best results regarding: plant height, stem diameter, leaves area, number of flowers, number of branches per plants and total yield per plant.